Natural Hybridization Between Quercus crassipes and Q. crassifolia (Fagaceae) Is a Key Process to Ensure the Biodiversity of Their Associated Lichen Community - Leticia Valencia-Cuevas; Jennie Melhado-Carboney; Efraín Tovar-Sánchez (Diversity)
Lichens are organisms whose dynamics take place on terrestrial substrates such as rock, dead wood, living plants, and soil. Living trees are used for lichens as structural support to access light. However, little is known about how the genetic traits of a host tree influence which lichen species grow on it and, consequently, the community structure of this funga. In this study, we investigated how the genetic diversity GD of host oak taxa (Quercus crassifolia, Q. crassipes and their putative hybrid: Q. × dysophylla) influence the community structure of the associated epiphytic lichen community in two hybrid zones (HZs) in Central Mexico. The lichen community was composed of 76 species, 27 genera and 14 families. We found significant differences in lichen composition between genetically distinct individuals and oak taxa in each HZ. Lichen diversity in Q. × dysophylla was intermediate and significantly different between parents in both HZs. We conclude that genetic differences between host oaks promoted significantly different lichen communities and that hybrids may act as ecological islands, accumulating lichen species from both parental species and their own novel species. Consequently, the conservation of HZs due to their high GD may be a strategy to ensure biodiversity conservation of oak-associated lichen communities.